Efektivitas Model Pembelajaran Problem Based Learning pada Mata Pelajaran Instalasi Motor Listrik - risha Nurul Maulidini; Aswardi Aswardi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2022)
This study aims to see the effectiveness of the Problem Based Learning (PBL) model on student learning outcomes in the subject of electric motor installation in class XI TITL SMKN 1 Kec. Guguak. The achievement of student learning outcomes in excessive competence is disappointing with the average student scoring below the SKM. one of the causes of the low grades of students is because the teacher-centred learning techniques are still being applied. As a result, students have difficulty understanding the material that is applied to students' failure in certain subjects. This study uses a quantitative approach with the type of Pre-Experimental using a one class posttest design. The object of this research is the Problem based learning (PBL) model and the effectiveness of learning outcomes that will occur in the subject of electric motor installation. The subjects in this study were students of class XI TITL at SMKN 1 Kec. Guguak. The research instrument used in this study was in the form of posttest questions in an objective form. As a result of the research giving the effect of posttest scores before applying the example of Problem-Based Learning is Good. Based on the results of the classical completeness test, namely Effective. It was concluded that the Problem Based Learning learning method was said to be effective because the classical completeness value was included in the High category.